2005
DOI: 10.1038/sj.onc.1209092
|View full text |Cite
|
Sign up to set email alerts
|

The elusive multiple self-healing squamous epithelioma (MSSE) gene: further mapping, analysis of candidates, and loss of heterozygosity

Abstract: The MSSE gene predisposes to multiple invasive but selfhealing skin tumours (multiple self-healing epitheliomata). MSSE was previously mapped to chromosome 9q22-q31 and a shared haplotype in affected families suggested a founder mutation. We have refined the MSSE critical region (o1 cM, o1 Mb) between the zinc-finger gene ZNF169 and the Fanconi anaemia gene FANCC. By genetic mapping we have excluded ZNF169 and FANCC as well as PTCH (PATCHED) and TGFBR1 (transforming growth factor beta receptor type-1) genes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…The condition was originally thought to be caused by a founder mutation, and linkage analysis of nine MSSE Scottish families identified a 4‐cM candidate region on chromosome 9q22–q31 5 . Loss of heterozygosity around this region was subsequently shown, suggesting that the MSSE gene might be a tumour suppressor gene 6 . The coding regions of the 14 known genes within the MSSE locus, including PTCH , ZNF169 and FANCC , were sequenced, but no mutation was identified 1 .…”
Section: Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…The condition was originally thought to be caused by a founder mutation, and linkage analysis of nine MSSE Scottish families identified a 4‐cM candidate region on chromosome 9q22–q31 5 . Loss of heterozygosity around this region was subsequently shown, suggesting that the MSSE gene might be a tumour suppressor gene 6 . The coding regions of the 14 known genes within the MSSE locus, including PTCH , ZNF169 and FANCC , were sequenced, but no mutation was identified 1 .…”
Section: Reportmentioning
confidence: 99%
“…5 Loss of heterozygosity around this region was subsequently shown, suggesting that the MSSE gene might be a tumour suppressor gene. 6 The coding regions of the 14 known genes within the MSSE locus, including PTCH, ZNF169 and FANCC, were sequenced, but no mutation was identified. 1 The XPA gene, mutations of which cause xeroderma pigmentosum, had already been excluded by a previous study.…”
Section: Reportmentioning
confidence: 99%
“…Two possible candidate genes in the region, xeroderma pigmentosum and PATCHED (mutated in familial basal cell carcinoma), were checked and excluded for mutations by Frances Richards in our group (115). Richards went on to exclude other candidates and to demonstrate loss of heterozygosity within the critical region in tumors, thus providing the first evidence that the MSSE gene was a tumor suppressor gene (7). Families with the condition were now being referred to us from Italy, Japan, Denmark, France, and the United States with linkage to 9q31 but with different haplotypes (19).…”
Section: Multiple Self-healing Squamous Epitheliomamentioning
confidence: 99%
“…TGFBR1 mutations in MSSE are functionally null implying a tumor suppressor action in this disease, whereas mis sense mutations in the same gene can lead to Marfan syndrome-related disorders (Goudie et al, 2011; Loeys et al, 2005). TGFBR1 had previously been excluded as a MSSE candidate because the gene lies outside the original shared at-risk haplotype (SRH) in the Scottish families (Bose et al , 2006). However using large scale sequencing technology, Goudie et al (2011) identified TGFBR1 germline mutations in a total of 18 MSSE families including 12 Scottish families.…”
mentioning
confidence: 99%